Pengaruh variasi konsentrasi larutan belimbing wuluh (Averrhoa bilimbi) terhadap uji aktivitas antimikroba secara In vitro - Desna Ayu Wijayanti; Osfar Sjofjan; Irfan H. Djunaidi (Faculty of Animal Science, Universitas Brawijaya, 2019)
The purpose of this research to determine the pH value and the antimicrobial activity of bilimbi extract (LBW) as a substitute for antibiotics. The method was field experiment using Completely Randomize Design with 4 treatments and 6 replications. The treatments were consist of P0(+) = antibiotic, P1= LBW 10%, P2= LBW 20% and P3= LBW 30%. Bilimbi extract used from bilimbi powder which is then dissolved. The measured variables were pH value and inhibition zone diameter of Escherichia coli, Salmonella sp. and Lactic Acid Bacteria. The data were analyzed by ANOVA and continued by Duncan’s Multiple Range Test (DMRT). The result of this research showed that LBW with higher concentration produces low pH value and the treatments between variation of concentration gave significantly different effect (P<0.01) on diameter of inhibition zone for Escherichia coli, Salmonella sp. and Lactic Acid Bacteria. The conclusion of this research was 30% concentration of LBW produces the lowest pH value, so that it can be inhibit the bacterial growth and has the potential as a substitute for antibiotics based on the result of antimicrobial activity that produces the best activity.